META-ANALISIS SKRIPSI MAHASISWA PENDIDIKAN FISIKA FKIP UNTAN TENTANG PELAKSANAAN REMEDIASI UNTUK MENGATASI MISKONSEPSI SISWA - Annuru, Melfa Pusparina; Marli, Haratua Tiur; Oktavianty, Erwina (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractFocus study on this meta-analysis was the effectiveness remediation of misconception. This study synthesized 51 thesis by bachelor students of physics education Tanjungpura University which published in Tanjungpura University library on 2013-2016 year period. It began reading abstract, the thesis body, and appendix. Then integrated data to a list of reading review as a means of gatherer data, and finally it analyzed. The average of effect size (ES) of all the thesis synthesized is 1,25 with various formula. The form of remediation implementation consists of re-teaching ( n = 47 ), feedback ( n = 1 ), interview ( n = 1 ), and integration ( n = 2 ). Based on stasistical analysis was obtained that IPK researchers, coefficients realibility, sampling method in this research have significant influence on effect size. The integration of remediation type is the most effective remediation activity which has effect size number 1.73. The result of the analysis research is expected to be consideration for overcoming student misconception remedial activity.Keywords: Meta-analysis, effectiveness, remediation, physics education